DeButts-Ely collection of Lee family papers
Correspondence, letterbooks, journal, scrapbook, memorandum book, reminiscence, clippings, and other papers pertaining primarily to Robert E. Lee and members of his family, including his wife, Mary Randolph Custis Lee. Subjects include Robert E. Lee's military career as an engineer in Missouri and Texas and as commander of the Confederate Army. Other family members represented include Daniel Parke Custis and Agnes (Eleanor Agnes) Lee.
Photocopies and enlargement prints of originals chiefly in the Virginia Historical Society (Richmond).
Virginia Historical Society
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Custis, Daniel Parke, -- 1711-1757.; Lee, Agnes, -- 1841-1873.; Lee, Mary Randolph Custis, -- 1807-1873.; Lee, Robert E. -- 1807-1870.; Lee family; Confederate States of America. -- Army; United States. -- Army; Military engineering -- Missouri; Military engineering -- Texas; United States -- History -- Civil War, 1861-1865.